2020
DOI: 10.1039/d0ra03629c
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the structure-performance relationship of polyphthalamide (PPA) composites reinforced with high-temperature produced biocarbon

Abstract: Biocarbon-filled polyphthalamide composites were made, achieving comparable mechanical and thermal characteristics to talc-filled ones, at a lower density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…4 The volume fraction of the fiber was calculated using the densities of the composites, the matrix, and the fibers, as shown in eqn (5), and the volume fraction of the matrix is equal to (1– V f ). 33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The volume fraction of the fiber was calculated using the densities of the composites, the matrix, and the fibers, as shown in eqn (5), and the volume fraction of the matrix is equal to (1– V f ). 33 …”
Section: Resultsmentioning
confidence: 99%
“…In these equations, E m is the elastic modulus of the matrix, V m is the volume fraction of the matrix, E f is the elastic modulus of the fiber, and V f is the volume fraction of the fiber. 33 The elastic moduli of the polymer and the composites were calculated in this study, while the elastic modulus of the fiber was calculated in a previous study, estimated at 21.09 GPa. 4 The volume fraction of the fiber was calculated using the densities of the composites, the matrix, and the fibers, as shown in eqn (5), and the volume fraction of the matrix is equal to (1-V f ).…”
Section: Fiber/particle Size Distributionmentioning
confidence: 96%
“…Bone, meal and feather fillers can be produced for 4.4, 4.3 and 3.2 p/kg respectively. This is notably lower than for common polymer fillers such as calcium carbonate (purchase price of between 31 -39 p/kg (Lee et al, 2020)), talc (12 -51 p/kg (Gonzalez De Gortari et al, 2020)) or kaolin (13 p/kg (Jafari et al, 2020)). The final cost of poultry waste polymers is also lower than for oil-derived polymers, i.e.…”
Section: Energy Carbon and Cost Implicationsmentioning
confidence: 86%
“…Recently, our group investigated the use of a high temperature biocarbon (950 C) as filler in a PPA matrix, and compared the mechanical properties of the resulting composites with talc-filled ones with the same weight percentage. 90 We found that except for HDT, all the mechanical characteristics were retained at a lower density and were a key component in automotive applications where weight reduction is required in order to lower carbon dioxide emissions. The similarity of particle size between the biocarbon and talc was a key component in obtaining similar results, though more research is necessary to explain and explore which mechanisms if any, can explain the good compatibility between filler and PPA.…”
Section: Engineering Compositesmentioning
confidence: 93%
“…Recently, our group investigated the use of a high temperature biocarbon (950°C) as filler in a PPA matrix, and compared the mechanical properties of the resulting composites with talc‐filled ones with the same weight percentage 90 . We found that except for HDT, all the mechanical characteristics were retained at a lower density and were a key component in automotive applications where weight reduction is required in order to lower carbon dioxide emissions.…”
Section: Engineering Compositesmentioning
confidence: 99%